2021
DOI: 10.31891/2079-1372-2021-102-4-51-60
|View full text |Cite
|
Sign up to set email alerts
|

Basic approaches and requirements for the design of tribological polymer composite materials with high-modulus fillers

Abstract: Based on a combination of a system-oriented approach and a synergetic concept, the requirements for the design of tribological polymer composite materials with high-modulus fillers are formed. These materials are considered as an open dynamic system that evolves during operation. The principles of the synergetic concept for tribotechnical systems taking into account the theory of evolution and self-organization to ensure its self-governing and self-supporting development are considered. It is revealed that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…It is possible to predict that in PCM there is such a filler content when the value of its yield strength exceeds the value of the yield strength. In this case, the viscous nature of the destruction of PCM will turn into brittle fracture fracture [13]. In this case, equation (1) will change and take the form:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible to predict that in PCM there is such a filler content when the value of its yield strength exceeds the value of the yield strength. In this case, the viscous nature of the destruction of PCM will turn into brittle fracture fracture [13]. In this case, equation (1) will change and take the form:…”
Section: Resultsmentioning
confidence: 99%
“…; PCM  coefficient that takes into account the shear modulus and Burgers vector of the polymer matrix, as well as the size and shape of the filler particles in PCM [13,14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tribocoupling of parts made of polymeric composite materials (PCM) has shown their effectiveness in increasing the durability of systems and units of machines [1][2][3]. However, there is a problem of optimizing the composition of polymer composites from the content of fillers, the distribution of stress fields in the polymer matrix, the geometric shape and concentration of the filler and the development of methods for evaluating the efficiency and reliability of such tribocouples [4,5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is shown that in the PCM the main part of the load is received by the filler. Reinforcing fillers prevent the movement of dislocations in the matrix, which is subject to plastic deformation, limiting it [3]. Strengthening of PCM is carried out by increasing the content of the filler and reducing the distance between its particles.…”
Section: Literature Reviewmentioning
confidence: 99%